Pola Asuh Orangtua dalam Meningkatkan Budaya Belajar Anak di Desa Pancahan Baru Kecamatan Rao Selatan Kabupaten Pasaman - Sormin, Darliana; Samsidar, Samsidar; Mariani, Leli (Institut Agama Islam Negeri Padangsidimpuan, 2020)
This study aims to determine parenting styles in improving children's learning culture in Pancahan Baru Village, Rao Selatan District, Pasaman Regency, as well as what efforts should be given by the community so that children in this new enlightened village have a learning spirit so that a learning culture emerges from the children. . This research uses qualitative research and data collection techniques by means of observation, interviews, and documentation. Family is the first environment for children, family has a huge influence on children's learning success. There are many reasons why parents do not pay special attention to their children, including because they are busy working as farmers to meet the daily needs of the family and the parents' insufficient knowledge. Parents' upbringing plays an important role in enhancing the learning culture, because the way parents educate / care for children also affects children's learning styles. So in improving children's learning culture, it will depend on how the parenting styles are given to their children. The efforts made by parents are educating with habituation, advice, exemplary, reward and punishment